EDUKASI KESEHATAN DAN EKONOMI KREATIF BAGI PEMUDA KRISTEN MENUJU INDONESIA EMAS 2045 - Bestian Simangunsong; Endang Junita Sinaga; Lasmaria Nami Simanungkalit; Wolter Parlindungan Silalahi (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTThe health education and creative economy activities for Christian youth were carried out in Horison Ranggitgit Village, Parmonangan Subdistrict, North Tapanuli Regency. The village has a majority Christian population with a relatively high proportion of people in the productive age group. This condition presents a significant potential for village development, yet it is challenged by issues such as low understanding of reproductive health, limited nutritional knowledge, risks of stunting, and constraints in facing increasingly competitive economic challenges. This program aims to provide education on reproductive health and adolescent nutrition while also training creative economic skills to help shape a resilient generation toward Indonesia Emas 2045. The methods used include interactive lectures, practice-based training, and simple marketing strategies. The results of the community service program showed an increase in adolescents’ knowledge of reproductive health, a better understanding of nutrition as preparation for a healthy generation, and improved skills in developing creative business ideas based on local potential. This program is expected to become the foundation for the emergence of a healthy, productive, and independent village generation capable of contributing to sustainable of development. Keywords : Health Education, Creative Ekonomy. Christian YouthABSTRAK Kegiatan edukasi kesehatan dan ekonomi kreatif bagi pemuda kristen dilaksanakan di Desa Horison Ranggitgit, Kecamatan Parmonangan, Kabupaten Tapanuli Utara. Desa ini memiliki mayoritas penduduk Kristen dengan komposisi usia produktif yang cukup tinggi. Kondisi ini menjadi potensi besar bagi pembangunan desa yang memiliki permasalahan seperti rendahnya pemahaman kesehatan reproduksi, kurangnya pengetahuan gizi, risiko stunting, serta keterbatasan dalam menghadapi tantangan ekonomi yang semakin kompetitif. Kegiatan ini bertujuan memberikan edukasi kesehatan reproduksi dan gizi pemuda sekaligus melatih keterampilan ekonomi kreatif untuk membentuk generasi tangguh menuju Indonesia Emas 2045. Metode yang digunakan meliputi ceramah interaktif, dan pelatihan berbasis praktik serta strategi pemasaran sederhana. Hasil pengabdian menunjukkan adanya peningkatan pengetahuan remaja tentang kesehatan reproduksi, pemahaman gizi sebagai bekal persiapan generasi sehat, serta keterampilan mengembangkan ide usaha kreatif sesuai potensi lokal. Program ini diharapkan menjadi fondasi bagi lahirnya generasi desa yang sehat, produktif, dan mandiri, sehingga mampu berkontribusi pada pembangunan berkelanjutan.Kata Kunci: Edukasi Kesehatan, Ekonomi Kreatif, Pemuda Kristen